Posyandu Information System in Payaman Village to Optimize Web-Based Health Services for Toddlers and the Elderly - Sugiarto, Elmalia Risma Putri; Riadi, Aditya Akbar; Susanto, Arief (Newinera Publisher, 2025)
The information system at Payaman Village Posyandu is currently still done manually by recording data using paper, making it vulnerable to errors in data processing and storage. This approach is less efficient, especially in managing registration data for toddlers and the elderly, as well as recording health history which is often not well documented. To overcome this problem, a website-based information system was developed which aims to increase efficiency and accuracy in the Posyandu administration process. This system is designed to make it easier to register participants, monitor the growth of toddlers and the health of the elderly in a more structured and well documented manner and carried out well by staff. The main users of this system are posyandu officers and village midwives who have access to health data and patient examination history. This system was built using the Waterfall software development method, with PHP and MySQL-based technology as the database. This system allows online registration to be carried out by Posyandu officers, central management of health data, and automatic creation of health history recapitulation reports. With this system, the Posyandu service process can be carried out more effectively, efficiently and transparently. In addition, the data stored in the system can be used for more accurate analysis of village community health. The implementation of this system is expected to improve the quality of health services at the Payaman Village Posyandu, reduce the risk of recording errors, and provide benefits for health workers in monitoring patient conditions on an ongoing basis.